Atypical healing of periapical lesions – report of three clinical cases - Bołtacz-Rzepkowska, Elżbieta; Tkaczyński, Piotr; Łęski, Michał (Journal of Stomatology, 2016)
Introduction. Long-term follow-up assessment of endodontic treatment is based on monitoring the healing process of periapical tissues. Full recovery in tissues surrounding the root apex is classified as a success, whereas lack of improvement is regarded as a failure. However, categorizing some of the clinical cases is more challenging, and thus intermediate aspects can be identified: incomplete or on-going healing, asymptomatic and functional state. Aim of the study. To present three cases of atypical periapical healing following both conservative and surgical endodontic treatment. Conclusions. In the majority of cases, inflammatory periapical lesions heal within 2 to 4 years after termination of treatment. If after this period a tooth remains asymptomatic but is associated with periradicular radiolucency, an eventuality of scar tissue or on-going healing has to be considered. Thorough diagnosing based on treatment history, anamnesis and clinical examination, long-term observation, and comparative analysis of radiographs can prevent an unnecessary intervention (endodontic retreatment or surgery).